The GLC7 type 1 protein phosphatase is required for glucose repression in Saccharomyces cerevisiae. - Tu, J (1994)
We cloned the GLC7/DIS2S1 gene by complementation of the cid1-226 mutation, which relieves glucose repression in Saccharomyces cerevisiae. GLC7 encodes the catalytic subunit of type 1 protein phosphatase (PP1). Genetic analysis and sequencing showed that cid1-226 is an allele of GLC7, now designated glc7-T152K, which alters threonine 152 to lysine. We also show that the glc7-1 and glc7-T152K alleles cause distinct phenotypes: glc7-1 causes a severe defect in glycogen accumulation but does not relieve glucose repression, whereas glc7-T152K does not prevent glycogen accumulation. These findings are discussed in light of evidence that interaction with different regulatory or targeting subunits directs the participation of PP1 in diverse cellular regulatory mechanisms. Finally, genetic studies suggest that PP1 functions antagonistically to the SNF1 protein kinase in the regulatory response to glucose.